Genetic aspects of congenital nephrotic syndrome: a consensus statement from the ERKNet-ESPN inherited glomerulopathy working group - Lipska-Ziętkiewicz, Beata S.; Ozaltin, Fatih; Hölttä, Tuula; Bockenhauer, Detlef; Bérody, Sandra; Levtchenko, Elena; Vivarelli, Marina; Webb, Hazel; Haffner, Dieter; Schaefer, Franz; Boyer, Olivia (European journal of human genetics, 2020)
Congenital nephrotic syndrome (CNS) is a heterogeneous group of disorders presenting with massive proteinuria within the first 3 months of life almost inevitably leading to end-stage kidney disease. The Work Group for the European Reference Network for Kidney Diseases (ERKNet) and the European Society for Pediatric Nephrology (ESPN) has developed consensus statement on genetic aspects of CNS diagnosis and management. The presented expert opinion recommends genetic diagnostics as the key diagnostic test to be ordered already during the initial evaluation of the patient, discusses which phenotyping workup should be performed and presents known genotype-phenotype correlations.